Clinical Aspects and Detection of Emerging Rickettsial Pathogens: A “One Health” Approach Study in Serbia, 2020 - Banović, Pavle; Díaz-Sánchez, Adrian A.; Simin, Verica; Foucault-Simonin, Angélique; Galon, Clemence; Wu-Chuang, Alejandra; Mijatović, Dragana; Obregón, Dasiel; Moutailler, Sara; Cabezas-Cruz, Alejandro (Frontiers in Microbiology, 2022)
Ticks carry numerous pathogens that, if transmitted, can cause disease in susceptible humans and animals. The present study describes our approach on how to investigate clinical presentations following tick bites in humans. To this aim, the occurrence of major tick-borne pathogens (TBPs) in human blood samples (n = 85) and the ticks collected (n = 93) from the same individuals were tested using an unbiased high-throughput pathogen detection microfluidic system. The clinical symptoms were characterized in enrolled patients. In patients with suspected TBP infection, serological assays were conducted to test for the presence of antibodies against specific TBPs. A field study based on One Health tenets was further designed to identify components of a potential chain of infection resulting in Rickettsia felis infection in one of the patients. Ticks species infesting humans were identified as Ixodes ricinus, Rhipicephalus sanguineus sensu lato (s.l.), Dermacentor reticulatus, and Haemaphysalis punctata. Five patients developed local skin lesions at the site of the tick bite including erythema migrans, local non-specific reactions, and cutaneous hypersensitivity reaction. Although Borrelia burgdorferi s.l., Babesia microti, Anaplasma phagocytophilum, and Candidatus Cryptoplasma sp. DNAs were detected in tick samples, different Rickettsia species were the most common TBPs identified in the ticks. The presence of TBPs such as Rickettsia helvetica, Rickettsia monacensis, Borrelia lusitaniae, B. burgdorferi, Borrelia afzelii, A. phagocytophilum and B. microti in ticks was further confirmed by DNA sequencing. Two of the patients with local skin lesions had IgG reactive against spotted fever group rickettsiae, while IgM specific to B. afzelii, Borrelia garinii and Borrelia spielmanii were detected in the patient with erythema migrans. Although R. felis infection was detected in one human blood sample, none of the components of the potential chain of infection considered in this study tested positive to this pathogen either using direct pathogen detection in domestic dogs or xenodiagnosis in ticks collected from domestic cats. The combination of high-throughput screening of TBPs and One Health approaches might help characterize chains of infection leading to human infection by TBPs, as well as prevalence of emerging rickettsial pathogens in the Balkan region.